The impact of multifactorial factors on the Quality of Life of Behçet's patients over 10 years - Senusi, Amal A.; Mather, John; Ola, Dennis; Bergmeier, Lesley A.; Gokani, Bindi; Fortune, Farida (Frontiers in Medicine, 2022)
Abstract Objective: This study analyses the 2020 survey and reviews the 2009, 2014 surveys to ascertain which Behçet’s symptoms, personal and family status, patients’ lifestyle, and work-related outcomes impacted on Health-Related Quality of Life (HRQoL). Methods: 459 Behçet’s patients submitted an online survey/questionnaire. Patients provided information on socio-demographic characteristics, disease duration, historical and current symptoms, systemic and topical medication, health related lifestyle, work-related outcomes regarding employment status and claiming benefits and QoL measured by EQ-5D index. Results: 419 patients met the inclusion criteria, and 371 who had full data [Males: Females: Others=84:285:2, mean-age=41.1±23.3:38±13.2:40±5] The main symptoms associated with patients seeking medical care were mouth ulcers 30% and genital ulcers 23%, joint 14% and eye problems 9%. The EQ-5D index for 2009, 2014, 2020 was (mean±SD); 0.47± 0.38, 0.42± 0.37, 0.34± 0.40 respectively p<0.05. 2020 patients had the worst values of the 5 domains compared to 2014 and 2009. Interestingly, mobility value was the same over the 10 years of monitoring patients. BS symptoms that had significant negative impact on QoL were; 2009 (arthropathy, neurological problems, pathergy reaction, and stomach/bowel symptoms), 2014 (arthropathy, headache, neurological problems, pathergy reaction, and skin lesions). 2020 (arthropathy, neurological problems, and stomach/bowel symptoms). The 2014 and 2020 surveys reported the QoL is significantly better in patients on immunosuppressant, who did sport, continued in employment and not receiving benefits. Conclusion: the main cause for the negative impact on BS patients QoL over the 10 years were join pain and neurological problems. In addition, sociodemographic (gender, age, marital and education status), lifestyle (medication, cannabis, drinking wine and regular exercise), employment status (employee and no career change), and accessing benefits (never claim benefit) all had a significant influence on patients’ HRQoL.